2004
DOI: 10.1007/s00464-003-9049-1
|View full text |Cite
|
Sign up to set email alerts
|

First experience of endoscopic implantation of tissue expanders in plastic and reconstructive surgery

Abstract: The advantages of the endoscopic implantation of tissue expanders are a reduction in expansion time, a shorter hospital stay, less patient discomfort, and the prevention of complications (hematoma, seroma, infection, wound dehiscence).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…Hence, there have been efforts to locate the incision further away from the expander pocket, while preserving the benefits of operating under direct vision. Sharobaro et al (5) suggested creating the pocket and placing the expander through a distant, small incision under endoscopic vision. They were able to accomplish shorter expansion time, low complication rates, and excellent wound healing of primary and postreconstructive wounds, demonstrating the benfits of distant incision placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there have been efforts to locate the incision further away from the expander pocket, while preserving the benefits of operating under direct vision. Sharobaro et al (5) suggested creating the pocket and placing the expander through a distant, small incision under endoscopic vision. They were able to accomplish shorter expansion time, low complication rates, and excellent wound healing of primary and postreconstructive wounds, demonstrating the benfits of distant incision placement.…”
Section: Discussionmentioning
confidence: 99%
“…Insertion of a balloon expander via a remote incision and using endoscopic techniques for the placement of the expanders is one alternative that has been shown to decrease postoperative complications. A more recent study that investigated the endoscopic approach demonstrated reduced time of expansion, time of hospitalization and patient discomfort (5). However, the costs and technological requirements associated with this technique are significant, which is a limiting factor in its widespread adoption.…”
mentioning
confidence: 99%
“…Therefore, we think this technique should be reserved for large, poor-quality burn alopecia. Recently, to overcome the drawbacks of scalp expansion surgery, various innovate techniques, such as supragaleal expansion, 22 sequential scalp expansion without interval, 23 endoscopic implantation of expanders, 24 and scalp expansion using self-filling osmotic tissue expanders, 25 have been introduced. We believe these new techniques can make scalp expansion surgery a more useful and reliable method for reconstruction of burn alopecia in the future.…”
Section: Annals Of Plastic Surgery • Volume 65 Number 3 September 2010mentioning
confidence: 99%
“…Die durchschnittliche Komplikationsrate bei Expanderimplantationen wird in der Literatur zwischen 5 und 39 %, vereinzelt bis zu 70% angegeben [11,14,26]. Typische Komplikationen bei konventioneller Technik der Expanderimplantation sind unter anderem Hämatombildung bei Nachblutung und Infektion des Expanders sowie Expanderleckage und Hautperforation [5,25].…”
Section: Diskussionunclassified